Complementarity among dragonflies across a pondscape in a rural landscape mosaic. Issue 3 (20th January 2019) - Briggs, Andrew J.; Pryke, James S.; Samways, Michael J.; Conlong, Des E.
Abstract: Networks of ponds (pondscapes) are becoming increasingly significant for resilient landscape planning in rural areas. Farmland and forestry ponds are habitat islands that support heterogeneous communities of aquatic organisms. Species richness, Dragonfly Biotic Index (DBI), Shannon's index, and species composition are used here to assess the complementary conservation value of adult dragonfly assemblages associated with forty ponds across a protected area‐sugarcane‐forestry mosaic. Despite differences in environmental variables among the various ponds, dragonfly species richness, DBI, Shannon index scores, as well as responses to particular environmental variables, did not differ between ponds in sugarcane, plantation forestry, and protected areas. Dragonfly composition differed in response to vegetation cover. Our results highlight the importance of catchment and regional management for all ponds within the pondscape, and show that ponds in the transformed areas (i.e. sugarcane and forestry areas) are important contributors to regional conservation. As the various ponds were complementary in their dragonfly assemblages, we recommend conservation focus at the level of the pondscape rather than on individual ponds.